Analisys Multitemporal Changing Mangrove's Area at Belitung Regency Bangka Belitung Island Province, Indonesia - Aulia, Beni (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research is to know the change of mangrove land at Belitung district by using remote sensing for mangrove land changes in 2001 and 2016 (multitemporal). Radiometric correction on this research aims to improve the quality of the image and at the same time improve the pixel values that do not correspond to the actual spectral values, dgunakn image is Landsat 7 Landsat 8 2001 and 2016. The composite image is used on the research of composite RGB bands 4, 5, and 3 for Landsat 7 as for Landsat 8 used composite RGB 5, 6 and 4. This research uses software ENVI 4.5 and Arcgis 10.1. The result of the interpretation of the map changes in the region. Mangrove forest area in 2001 was 10,032.75 Ha and 9,779.4 Ha found 2016. So, the shrinkage of mangrove land that is the lowliest coastal Belitung district is 253.35 ha.